Must ACP states continue to import what they can produce themselves? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Rural potential to be fully exploited The combined population of the ACP States will double over the next twenty years. How will these nations be able to feed themselves if a substantial part of their food has to be imported, especially as most of...